Non-statistical fragmentation of C60 and the formation of endohedral defect fullerenes. Issue 20 (January 2020) - Stockett, M H; Wolf, M; Gatchell, M; Schmidt, H T; Zettergren, H; Cederquist, H
Synopsis: We report the first observation of the endohedral defect fullerene complex He@C 59 − and the first measurement of the threshold displacement energy of a fullerene.